Extreme Precipitation Events in Summer in the Iberian Peninsula and Its Relationship With Atmospheric Rivers - Ramos, Alexandre M.; Martins, Maria J.; Tomé, Ricardo; Trigo, Ricardo M. (Frontiers in Earth Science, 2018)
This study identifies and characterizes the importance of the Atmospheric Rivers in the extreme precipitation episodes that strike the Iberian Peninsula and Portugal during the extended summer months (April to September) between 1950 and 2007. The extreme precipitation days are ranked taking into account a daily gridded precipitation database for the Iberian Peninsula at a 0.2º resolution. The ranking is based on the magnitude of the extreme precipitation days considering not only on the area affected above the 95th climatological percentile but also by the precipitation intensity within the anomalous area. The Atmospheric Rivers detection scheme is used for the North Atlantic Ocean basin that allows the identification of the persistent Atmospheric Rivers that impact the Iberian Peninsula for the extended summer months. It is shown, that there is a relationship between the Atmospheric Rivers and the extreme precipitation days in Portugal especially during the transition months of April, May and September. On the contrary when analysing the entire Iberia Peninsula the impact of ARs is considerably reduced. Moreover, the impacts of the Atmospheric Rivers is considerably higher for the top ranked events in Portugal but decreases when considering less intense extreme precipitation days.